PENGETAHUAN AKSEPTOR TENTANG KONTRASEPSI PIL - Suko Andini Saputr; Wahyu Margiyanti (OVUM : Journal of Midwifery and Health Sciences, 2021)
Family planning is one of the efforts carried out by the government with the aimof controlling the rate of population growth, so that it can contribute to improvingthe quality of human resources. Birth control pills or oral contraceptives pills arehormonal contraceptives in the form of drugs in the form of pills that are insertedby mouth (taken by mouth), containing the hormones estrogen and progesterone.Some women who take birth control pills still ovulate and get pregnant. This isdue to the indiscipline and knowledge of pill acceptors in consuming birth controlpills.The type of research is descriptive quantitative, the research location is in theIndependent Practice Midwife. The research sample was all family planningacceptors other than pills, as many as 67 acceptors using the Accidental Samplingtechnique. The research instrument used a questionnaire.Based on the data analysis, it was found that there were 39 people (58%), withsufficient knowledge about pill contraception, 23 respondents (34%), and 5respondents (8%) having less knowledge.The conclusion of the study shows that the description of WUS knowledge aboutpill contraception is mostly in the good category.